THE PLEISTOCENE GLACIATION RHYTHMS - Nikolaev S.D.; Pisareva V.V.; Sudakova N.G. (My University, 2003)
Our own and published paleogeographic data have been revised to reliably define rhythms and intensity of climatic events in the glaciation areas of the Russian Plain during the Brunhes Chron. Biostratigraphic and lithostratigraphic studies enable recognition of till horizons and other diagnostic features of seven Neopleistocene glaciations. The extreme distribution limits of morains are specified. The distribution areas of corresponding glacial sheets gradually decreased in the Russian Plain since the Don to the late Valdayan Glaciation time. The independent status of the Dnieperian and Moskowian glaciations remains a matter of controversy. Some stages of vegetation development in the central Russian Plain are outlined. Paleobotanical data have been used to reveal the short-term and longer climatic rhythms. These data also show that the Akulovo Interglacial is an Early Eopleistocene event. Complex paleogeographic patterns of the post-Don interglacial epochs are described. The established comparative intensity of climatic events in the corresponding latitudinal zones of continent and oceans has been used to correlate the Valdayan, Moskowian, Dnieperian, Okaian, Don, and Setun' glacials with the oxygen-isotope stages 2-4, 6, 8, 12, 14, and 16, respectively. Correlation between shorter-term climatic events in continental and oceanic regions is detectable in the post-Don period.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен